Analysis of Environmental Microbiology of the Green Mussels (Perna viridis) Culture in the Waters of Tanjung Kait, Tangerang, Banten - Mustahal Mustahal; Shiva Vauziah; Forcep Rio Indaryanto; Swastika Dita Soraya (Jurnal Perikanan dan Kelautan, 2019)
Microbiology parameter is one important factor for the success of green mussels culture. Characteristic of green mussels as the filter feeder might be contaminated easily by the diluted toxin as well as the carrier of  pathogens. This research aims to find out the amount of contamination of pathogenic bacteria. Samples of water and the green mussels were taken from the waters of Tanjung Kait, Tangerang, Banten and were then identified in the Laboratory of Fish Diseases Investigation  and Environment in Pasauran, Serang. Analysed bacteriological parameters were total Coliform, as well as the species of E coli, Salmonella sp., a total of aerobic bacteria and Vibrio. The result of seawater quality and green mussel showed that the total abundance of Coliform cell was lower than <3 until 240 MPN/ml in water and about 8,3 until >1600 MPN/g in green mussel, E.coli was < 3 until 43 MPM/ml in water and 0,18 until 130 MPM/g in green mussel, negative result for Salmonella sp. neither in water nor in green mussels. Total aerobic bacteria was found about 34-880 x102 CFU/ml in water, 24-980 x104 CFU/ml in the sediment and 12-100 x107 CFU/ml in green mussel. The result of Vibrio in water was about 50-340 CFU/ml, 4,4-88 x102 CFU/g in sediment and 0,082-25 x104 CFU/ml in the green mussels. Salmonella was found the negative test results in accordance with predefined standards, both with the seawater quality standard based on biological parameters and SNI 7388-2009 regarding the limit of microbial contamination of foods, while for other pathogenic bacteria parameters still above the predefined standard.